CARTOONS AS AN ADDITIONAL RESOURCE FOR TEACHING ENGLISH (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
Cartoon comes from an Italian word ‘Cartone’ meaning a large paper. It has developed into a powerful medium not only for entertainment but also for education. In language learning, cartoons can help simplify complex concepts and engage students in meaningful ways. Many studies have proven that cartoons positively influence student motivation and understanding. However, the process of designing cartoons that align specifically with English Structure lessons remains underexplored. This article presents a design and development research focusing on how a cartoon can be constructed as a supplementary material in the context of teaching English grammar. The study outlines the stages of planning, drafting, and producing educational cartoons that reflect key grammatical points. The final product of this research is a cartoon entitled “Coraline in the country of nightmares” which integrates various English sentence structures into engaging and visually appealing scenarios.